THE AGRARIAN POVERTY PARADOX AND GOVERNANCE FRAGILITY: EVALUATING RURAL SOCIAL ASSISTANCE UNDER DECENTRALIZED OVERSIGHT - Zohrawati Buntuang Mutia; Ely Ibrahim; Siskawaty Yahya (Journal of Economic, Business, and Administration (JEBA), 2026)
This research aims to: 1) Evaluate the effectiveness and targeting accuracy of the government's social assistance program in Sukma Village, Botupingge District, Bone Bolango Regency; 2) Analyze the coordination and oversight dynamics between the Village Government and the Village Representative Body (BPD); and 3) Identify the administrative and sociological factors hindering the program from reducing poverty rates. This study employs a qualitative approach with an intrinsic case study design. Data were collected through field observations, documentation, and structured interviews with key informants (Village Head, Village Secretary, BPD, Hamlet Rulers, and farming households). The results indicate that the implementation of the social assistance program in Sukma Village is currently suboptimal, facing a profound socio-economic poverty paradox. This ineffectiveness is driven by rigid, macro-level national poverty indicators that fail to match the volatile economic realities of corn and bean farmers. Institutionally, the functional shift of the BPD from an independent watchdog into an advisory partner has weakened the local system of checks and balances, reducing the Integrated Social Welfare Data (DTKS) verification into a mere administrative formality. Furthermore, acute digital infrastructure deficits (only 3 laptops available) and a deeply embedded dependency mindset among residents—who view aid as a permanent subsidy act as primary barriers stalling rural economic independence. The findings suggest that a shift toward rights-based participatory governance and comprehensive village data digitalization is required to optimize targeting efficiency.